Tansformasi Pembelajaran Pendidikan Agama Islam Melalui Pendekatan Humanistik di Sekolah Menengah Atas - Rahma Alya; Neni Neni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The transformation of Islamic Religious Education (PAI) learning in senior high schools has become an urgent necessity in response to the demands of modern education that emphasize humanistic and student-centered learning. This study aims to describe the implementation of a humanistic approach in PAI learning, analyze its impact on students’ development, and identify supporting and inhibiting factors in its classroom application. This research employed a qualitative approach with a case study design. Data were collected through classroom observations, in-depth interviews with PAI teachers, questionnaires distributed to students, and document analysis of lesson plans and instructional materials. The findings reveal that the implementation of dialogic, reflective, and experience-based learning strategies creates a more comfortable and engaging learning environment. Students feel more appreciated, gain opportunities to express their ideas, and demonstrate improvements in learning autonomy, self-confidence, and moral responsibility. In addition, teachers increasingly integrate cognitive, affective, and spiritual dimensions into instructional planning, making PAI learning more relevant to real-life contexts. These results indicate that the humanistic approach not only enriches the learning process but also contributes significantly to the comprehensive and sustainable development of students’ character.